(untitled) (Pain medicine, 2022)
WHO estimates that the prevalence of headaches worldwide in the adult population is approximately 50 %. Globally, half to threequarters of people aged 18 to 65 have complained of headaches in the past year, and more than 30 percent have suffered from migraines. At the same time, 1.7 to 4 % of the adult population suffers from headaches that last 15 or more days a month. Undoubtedly, cephalgia constitutes a global problem. However, it is worrying that the causes of headaches are not always correctly diagnosed. The main clinical barrier pointed out by WHO is the lack of knowledge of health professionals about headache management. Thus, the broad coverage of issues related to the management of patients with cephalgia does not lose its relevance, and even more: it needs to be supplemented with current data. In particular, the mechanisms of headache can be associated with several pathophysiological processes that are triggered by the influence of professional activities, specific physical activity, active leisure, or amateur sports. Recreational diving has become a popular form of active leisure for the past 20 years. It is noteworthy that headache is a common symptom in divers and, although it is usually benign, it can sometimes signal the serious consequences of high pressure. Proper diagnostic tactics require specialists to carefully collect the anamnesis and examine the patient, as well as to understand the unique physiological changes in the human body that occur under the influence of underwater environmental factors.